Characterisation of phosphotransferase systems (PTS) in Clostridium difficile - Bollard, Niall (2018)
Phosphotransferase systems (PTS) represent an important method of sugar uptake in bacteria and have been well described in the past. However, research into PTS within the genus Clostridium has been mainly restricted to the non-pathogens. Analysis of the genome of Clostridium difficile 630 revealed over 40 intact PTS; this is over three times as many as in other pathogenic Clostridia, such as Clostridium perfringens and Clostridium botulinum. Previously, carbon catabolite repression has been shown to affect toxin production in C. difficile. Being capable of utilising different carbohydrates efficiently could be important for C. difficile to adapt to, grow, and survive in the human gut. So far, little work has been done to corroborate the role of individual PTS in carbohydrate uptake, sensing of environmental stimuli and regulation of virulence, i.e. toxin expression. A deeper understanding of the PTS in C. difficile, and their importance in virulence, could lead to the development of new drug targets.